Development of a Digital Calibration Test System for Flickermeter - Sia, Lih Huoy (2007)
Over last few decades, there has been deterioration in the power quality due to the increase in non-linear domestic and industrial loads usage. There may be a systematic low frequency variation of the voltage envelope or a series of random voltage changes, which the magnitude may not normally exceed the voltage regulations laid down by the supply authority. These phenomena known as voltage flicker have severe effect on power quality. Flickermeter is the power analyzer for measuring the voltage flicker, flicker sensation and flicker severity index. International Electrotechnical Commission (IEC) has published IEC 61000-4-15 standard describing the functional and design specifications for flickermeter. Most of the flickermeter and flickermeter calibration test systems presented in the literature are based on analog signal processing techniques. In this thesis, a digital calibration test system for flickermeter based on digital signal processor (DSP) is presented. The system has been developed around DSP TMS320 and test signals required as per IEC 61000-4-15 standard to test a flickermeter is generated. A DSP based waveform generator, which can give sine, square, triangular waveform with frequency of operation from 0.01 Hz to 24 kHz has been described in this thesis. The DSP starter kit (DSK) TMS320C6713DSK with Code Composer Studio and C programming language had been used in obtaining the desired signal. Amplitude modulated test signals with different modulation index as per IEC 61000-4-15 standard had been generated using DSP based waveform generator. A measurement system was developed to capture the analog signals generated by DSP starter kit. LabVIEW had been used to perform the data analysis and from which voltage fluctuation for P and Pst measurement was obtained. For the voltage fluctuation of P measurement, it was found that the percent modulation of test signals measured by the oscilloscope is from 2.15% to 8.20% for sinusoidal modulating frequency; and 0.67% to 7.65% for rectangular modulating frequency. The average of the difference between the test signals generated and IEC standard value was 4.6% for sinusoidal voltage fluctuation; and 3.9% for the rectangular voltage fluctuation. For the voltage fluctuation of Pst measurement, it was found out that test signals generated are 2.8% deviated from IEC standard. The digital calibration test system developed was able to generate test conditions which were within 5% from the standard values required for testing.